Visual Hallucinations Induced by Clarithromycin in a Child: A Case Report and Literature Review. Issue 4 (July 2019) - Göktürk, Bahar; Erden, Semih
Abstract : Objective: Our aim was to present a child with visual hallucinations possibly associated with oral clarithromycin administration. Case report: A 4-year-old child was admitted to our hospital with an onset of visual hallucinations after taking the second dose of clarithromycin by mouth. The symptoms gradually disappeared in a week once the clarithromycin therapy had been discontinued. She was observed for a month without any symptoms or further treatment. She was suspected of having Hoigne syndrome (also called as antibiomania) induced by clarithromycin syndrome. Conclusion: This report highlights neuropsychological adverse effects due to therapeutic doses of clarithromycin therapy as a possible adverse effect in children.